2018
DOI: 10.1016/j.compbiomed.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between carotid artery sclerosis and blood pressure variability in essential hypertension patients

Abstract: Objectives: This study aimed to investigate the relationship between the presence of carotid arteriosclerosis (CAS) and blood pressure variability (BPV) in patients with essential hypertension. Methods:One hundred and forty four essential hypertension patients underwent ambulatory BP monitoring for 24 hours after hospitalization. Common BPV metrics were calculated. General clinical parameters, including age, gender, height, weight, history of coronary heart disease, stroke, diabetes, hypertension, smoking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…These data are broadly consistent with the global trend in lower middle-income countries [21]. Well known that BP VVV is associated with cardiovascular risk factors [24], AH-mediated target organ damage [12,13,[25][26][27] and major adverse CVD events [9,10,28], thus seems to be of crucially importance at different stages of CVD continuum. The present study, enrolled predominantly young and middle-age males with uncomplicated AH, demonstrated that HBPV was associated with more pronounced AH-mediated subclinical target organ damage, namely the LV mass index, carotid arteries and kidneys, which was in agreement with other available studies [12,13,[25][26][27].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These data are broadly consistent with the global trend in lower middle-income countries [21]. Well known that BP VVV is associated with cardiovascular risk factors [24], AH-mediated target organ damage [12,13,[25][26][27] and major adverse CVD events [9,10,28], thus seems to be of crucially importance at different stages of CVD continuum. The present study, enrolled predominantly young and middle-age males with uncomplicated AH, demonstrated that HBPV was associated with more pronounced AH-mediated subclinical target organ damage, namely the LV mass index, carotid arteries and kidneys, which was in agreement with other available studies [12,13,[25][26][27].…”
Section: Discussionsupporting
confidence: 87%
“…Well known that BP VVV is associated with cardiovascular risk factors [24], AH-mediated target organ damage [12,13,[25][26][27] and major adverse CVD events [9,10,28], thus seems to be of crucially importance at different stages of CVD continuum. The present study, enrolled predominantly young and middle-age males with uncomplicated AH, demonstrated that HBPV was associated with more pronounced AH-mediated subclinical target organ damage, namely the LV mass index, carotid arteries and kidneys, which was in agreement with other available studies [12,13,[25][26][27]. Moreover, HBPV was also associated with more advanced hypertensive retinopathy, that may reflect potential pathophysiological associations of BP variability with retinal microvascular abnormalities in AH [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated the association between short-term BPV and intracranial IPH in ischemic stroke with intracranial atherosclerosis. The results in our study revealed the following key findings: (1) the distinct effects of blood pressure and its variability on atherosclerosis in different population 25,26) . In young patients without end organ damage, blood pressure management is more important, however, in those hypertensive patients who have already presented multi-organ damage, BPV is much more important in predicting short-term stroke risk.…”
Section: Discussionsupporting
confidence: 57%
“…Full‐text versions of the remaining 73 articles were retrieved and singularly examined. Ultimately, 47 studies were excluded and, of the remaining 26 papers that were included, 22 were selected for quantitative analysis . Secondary endpoints (i.e.…”
Section: Resultsmentioning
confidence: 99%